Pengaruh Dana Pihak Ketiga dan SWBI terhadap Return Pada Bank Syariah Studi Kasus Pada PT Bank Mandiri Syariah, Tbk Periode Maret 2009 s.d. Juni 2013 - Muhammad Luthfi (Universitas Malahayati, 2013)
Islamic banking in Indonesia has experienced rapid growth in which the principles of sharia or the results have proved its resilience against t he economic crisis. This study aims to determine th e effect of third-party funds and SWBI to return (inc ome mudharabah and Musyarakah). The results of this study indicate that the third-party funds have a significant positive effect on the return to the significance of the results t count 0,019 and 2,246 SWBI have a significant negative e ffect on the results of t count return of -2.789 to 0.008 sebesar significance. Ta ken together SWBIs deposits and have an influence on the return. Keywords; Third Party Funds, Return and SWBI